(3GdRHO ef SdhI GdCMRGfs - (3eLghds; (3GdeHGQc Hf cGed Hf eMeO Hf GdMSjf GdHZOGOj GdXaQj, CHh HcQ GdNaGa,J (B543 (3g` s
(3ChdgG (B:s
(3bGd GdNWjH bO OYhJ Gddg JYGdi Cf jVjY ef CVGY SQi s
(3BNQgG (B:s
(3hJMJ JUQag Edi GdeeGJ hef HYOg dChdGOg heG bO CUGHgG s
(3GdfSNI HgG MhGTs
(3SdhI GdCMRGf GfXQ cTa GdXfhf L (B2 (3U`(B999s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs